Guaianolide Sesquiterpenes With Significant Antiproliferative Activities From the Leaves of Artemisia argyi - Ming, Wenzhuo; Zhang, Yi; Sun, Yiwei; Bi, Guangming; Su, Jing; Shao, Zhutao; Meng, Dali (Frontiers in Chemistry, 2021)
ABSTRACT: Four new guaiane-type sesquiterpenes, argyin H-K (1-4), as well as two known analogues (5 and 6) were isolated from the leaves of Artemisia argyi Lévl et Vant. The new compounds were characterized by the basic analysis of the spectroscopic data obtained (1H NMR, 13C NMR, HMBC and NOESY experiments) and their absolute configurations were determined by empirical approaches, combined with exciton chirality method and electronic circular dichroism calculations. To further understand the antitumor effects of A. argyi, the antiproliferative activities of these compounds against A549, MCF-7 and HepG2 cell lines were tested in vitro using CCK-8 assays. The results showed that these compounds had significant antiproliferative effects on MCF-7, with IC50 values of 15.13-18.63 μM, respectively, which were superior to oxaliplatin (IC50 22.20 μM). The results of molecular docking also confirmed the activities and revealed these compounds had strong binding with target protein.